Service quality in maritime transport : conceptual model and empirical evidence - Thai, Vinh Van (2013)
The purpose of this paper is to extend knowledge on service quality and how it is defined and thus, managed, in the context of maritime transport by proposing and testing a new conceptual model of service quality.